Anayasa Mahkemesinin Kamil Serdar Oğur ve Gülhan Oğur Kararı, Başvuru Numarası: 2014/7273, Karar Tarihi: 20.04.2017 Karar İncelemesi - Aykut, Gökhan (Seçkin Yayıncılık, 2017)
The fact that the merits of the case couldn’t be examined for many years by virtue of judgments regarding –rejection of venue and lack of jurisdiction given by different court different courts resulted in violation of right to trial within a reasonable time and such a situation is unacceptable in a state of law. The judgment of the Constitutional Court dated 20.04.2017 has been examined in this scope and we came to the same conclusion with the Constitutional Court that to spend nearly 5 years to fulfill the procedural shortcomings because of misjudgments would be a violation of right to trial within a reasonable time.
Keywords: Judicial Remedy, Lack of Jurisdiction, Lack of Competence, the Right to a Fair Trial, the Right to Trial within a Reasonable Time